SPE Rocky Mountain Regional Meeting 1983
DOI: 10.2118/11847-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Flooding-Design of a Low Cost, Portable Facility

Abstract: Chemical enhanced oil recovery projects usually require fairly soft water to achieve optimum recovery. Chemical softening was selected for an alkaline flood design in a Montana Muddy formation at a considerable savings over ion-exchange softening. Many Rocky Mountain oil fields have relatively soft water available, often from the producing formation. This paper shows that using simple and controllable processes with common oilfield equipment, satisfactory water treatment can be achieved at economic levels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(B.garrett, vankirk) 20 indicated that alkaline flooding needs high quality light water, therefore, ion exchange was widely performed in many fields of California for alkaline flooding at hardness levels of (2,000 ppm) where sodium cation is used to replace (Ca and Mg) on zeolite or organic gum.…”
Section: Case Studymentioning
confidence: 99%
“…(B.garrett, vankirk) 20 indicated that alkaline flooding needs high quality light water, therefore, ion exchange was widely performed in many fields of California for alkaline flooding at hardness levels of (2,000 ppm) where sodium cation is used to replace (Ca and Mg) on zeolite or organic gum.…”
Section: Case Studymentioning
confidence: 99%
“…Garrett et al 18 described an alkaline flood system using caustic precipitation, instead oflime treatment or ion exchange, to soften produced water. These systems typically operated at a pH greater than 12 to achieve excess caustic concentration for alkaline flooding.…”
Section: Caustic Precipitation Process At Aelrldgementioning
confidence: 99%